2014
DOI: 10.1111/petr.12409
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal renal function in pediatric heart transplant recipients: 20‐years experience

Abstract: This study was initiated to assess the temporal trends of renal function, and define risk factors associated with worsening renal function in pediatric heart transplant recipients in the immediate post-operative period. We performed a single-center retrospective study in children ≤18 yr receiving OHT (1993-2012). The AKIN's validated, three-tiered AKI staging system was used to categorize the degree of WRF. One hundred sixty-four patients qualified for inclusion. Forty-seven patients (28%) were classified as h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
1
5
1
Order By: Relevance
“…Our finding that 3% of patients required dialysis in the first post‐transplant year is higher than those reported in earlier pediatric cohorts but lower than that reported by contemporary single‐center studies of broader HT populations . Linking the Scientific Registry of Transplant Recipients (SRTR) and United States Renal Data System datasets, Choudhry et al recently reported the need for dialysis occurred in 4% of pediatric heart transplant patients over an 11.8‐year follow‐up period and that having a history of VAD support was nearly twice as common in patients who did not require dialysis .…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…Our finding that 3% of patients required dialysis in the first post‐transplant year is higher than those reported in earlier pediatric cohorts but lower than that reported by contemporary single‐center studies of broader HT populations . Linking the Scientific Registry of Transplant Recipients (SRTR) and United States Renal Data System datasets, Choudhry et al recently reported the need for dialysis occurred in 4% of pediatric heart transplant patients over an 11.8‐year follow‐up period and that having a history of VAD support was nearly twice as common in patients who did not require dialysis .…”
Section: Discussioncontrasting
confidence: 61%
“…In our study, these patients were older and more likely to be male. Three percent of patients in this study required dialysis at some point in the first post‐transplant year, mostly in the first 30 post‐operative days, which is less frequent than that reported for adults or the pediatric heart failure population in general . Lower pre‐implant eGFR was associated with post‐transplant CKD.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Acute kidney injury (AKI) in children is associated with increased length of stay (LOS), re‐hospitalization, mortality, and the development of chronic kidney disease (CKD) 1–7 . In the pediatric heart transplant (HT) population, persistent AKI has been associated with an increased risk of CKD within the first year after the transplant 8–10 .…”
Section: Introductionmentioning
confidence: 99%